Effects of Mercury Chloride on the Cerebral Cortex of Adult Wistar Rats (Journal of Experimental and Clinical Anatomy, 2009)
Mercury is among the heavy metals that have been reported to cause devastating health problem worldwide. The primary site of action of mercury chloride is the central nervous system. This study investigated the effect of mercury chloride on the cerebral cortex of adult Wistar rats. Twenty-four (24) adult Wistar rats were used for this study. Following four (4) weeks of acclimatization, the rats were randomly divided into five groups of five animals per group. The animals were allowed free access to food and water throughout the period of experiment. Group 1 was the control group and was administered distilled water, while groups 2, 3, 4 and 5 were administer 6.6mg/kg, 13.2mg/kg, 26.3mg/kg and 52.2mg/kg body weight of mercury chloride solution orally respectively for eight (8) days. After the period of mercury chloride administration, the animals were anaesthetized using chloroform and where sacrificed. The brain was fixed in Bouin's fluid and the tissue processed and stained with haematoxylin and eosin stains and were studied under the microscope. The photomicrographs reveal distortion and diffusion of cells and a widespread necrosis of the cortical neurons.